2012
DOI: 10.1002/ejsp.1894
|View full text |Cite
|
Sign up to set email alerts
|

A new American dilemma? The effect of ethnic identification and public service on the national inclusion of ethnic minorities

Abstract: Three experiments integrate research from political science and social psychology to examine the consequences of two competing visions of American national identity. American identity has been defined not only in terms of shared ethnocultural heritage originating in Europe (the ethnocultural prototype) but also in terms of shared commitment to civic service (the civic responsibility prototype). Three experiments tested the consequence of highlighting each of these national prototypes on perceivers' inclusion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
54
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 71 publications
(173 reference statements)
2
54
0
1
Order By: Relevance
“…However, endorsement of multicultural principles does not fit with recent evidence which shows that people dislike ethnic minorities who express their ethnic identity compared to others who downplay it (Dovidio, Gaertner, Schnabel, Saguy, & Johnson, 2010;Kaiser & Pratt-Hyatt, 2009;Yogeeswaran, Dasgupta, & Gomez, 2011). For example, Kaiser and Pratt-Hyatt (2009) demonstrated that Whites exhibit greater prejudice toward ethnic minorities who are strongly identified with their ethnic group compared to their weakly identified counterparts.…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…However, endorsement of multicultural principles does not fit with recent evidence which shows that people dislike ethnic minorities who express their ethnic identity compared to others who downplay it (Dovidio, Gaertner, Schnabel, Saguy, & Johnson, 2010;Kaiser & Pratt-Hyatt, 2009;Yogeeswaran, Dasgupta, & Gomez, 2011). For example, Kaiser and Pratt-Hyatt (2009) demonstrated that Whites exhibit greater prejudice toward ethnic minorities who are strongly identified with their ethnic group compared to their weakly identified counterparts.…”
mentioning
confidence: 82%
“…We assessed the degree to which participants construed Native-Americans as a group as legitimately American using 7 items adapted from previous research (Devos & Banaji, 2005;Yogeeswaran et al, 2011). Specifically, these items assessed the extent to which participants believed that NativeAmericans "belong in the U.S.," "are patriotic to the U.S.," "feel loyal to the U.S.," "respect America's political institutions and laws," "defend the U.S. when criticized," "work for the country's best interests," "identify with the U.S.," and "are truly American" (α = .85).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The civic, more inclusive, conception of national identity defines citizenship based on living within the national territory, following societal rules and laws, endorsement of equal political rights, and active participation and contribution to the society (Reijerse et al, 2012). Research showed that ethnic conceptualizations of the national identity are associated with more negative attitudes towards immigrants (Pehrson, Brown, & Zagefka, 2009;Pehrson, Vignoles, & Brown, 2009;Reijerse et al, 2012), while civic representations are related to prosocial orientations towards immigrants (Wakefield et al, 2011) and to more positive attitudes towards them (Reijerse et al, 2012;Yogeeswaran, Dasgupta & Gomez, 2012).…”
Section: Whether We Need Them: Depends On How Inclusive We Arementioning
confidence: 99%
“…By contrast, identity threats refer to concerns over the ingroups' uniqueness, values, and distinctiveness (Riek et al, 2006;Stephan et al, 1999). As people are motivated to see their own group as positively distinct from other outgroups (Taj fel & Turner, 1986), threats to the ingroup's distinctiveness, uniqueness, or identity have been found to elicit prejudice and discrimination (Jetten, Spears, & Manstead, 1997, 1998Yogeeswaran, Dasgupta, & Gomez, 2012). When robots are sufficiently humanlike and integrated into society, they may not only be perceived as a realistic threat to human jobs and resources but may also be perceived as threatening human identity by blurring the lines between what is human and what is machine.…”
mentioning
confidence: 99%